Pengaruh Lingkungan Sosial Terhadap Pembentukan Perilaku Anak Panti Asuhan Puteri Daerah Aisyiyah Kota Medan - Sinaga, Mutiara Annisa; Putri, Malida; Lubis, Mia Aulina (Universitas Muhammadiyah Sumatera Utara, 2024)
Childcare is an obligation that must be carried out by the family. This research focuses on the influence of the social environment to behaviour forming of children at Puteri Daerah Aisyiyah Orphanage in Medan, so it was conducted at the orphanage because there are social phenomena in the form of prosocial and antisocial behaviour. This study used a quantitative approach and correlation analysis method by sampling using the total sampling method is all 39 children. Data collected using a questionnaire. Hypothesis testing in this study uses single linear regression analysis with a partial test (T test). The results of simple linear regression analysis show that the independent variable is the Social Environment has a positive and significant influence to behaviour forming of children at Puteri Daerah Aisyiyah Orphanage in Medan with a t-count value t-table (5.346 2.026192) which means H0 is rejected and Ha is accepted with a significance value of t 0.05 (0.000 0.05). The results of simple linear regression analysis show that the equation Y = 13.366 + 0.408X which means a = 13.366 and b = 408. The result of the calculation of the coefficient of determination (R Square) test is 0.436.Keyword: Influence, Children, Social Environment, Behavior Forming, Orphanage